2005
DOI: 10.1136/sti.2004.012468
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of sex work

Abstract: Objective: To compile a global typography of commercial sex work. Methods: A Medline search and review of 681 ''prostitution'' articles was conducted. In addition, the investigators pooled their 20 years of collected papers and monographs, and their observations in more than 15 countries. Arbitrary categories were developed to compile a workable typology of sex work. Results: At least 25 types of sex work were identified according to worksite, principal mode of soliciting clients, or sexual practices. These ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
229
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(236 citation statements)
references
References 37 publications
4
229
2
1
Order By: Relevance
“…Loverboys can also threaten to inform the girl's family about her activities. In line with Harcourt and Donovan's (2005) findings, women can also be forced to work extra shifts when they have not earned enough money. In this context, they often work below the normal price or procure unprotected sexual services in order to obtain the required earnings, which in turn affects business in the RLD generally…”
mentioning
confidence: 55%
“…Loverboys can also threaten to inform the girl's family about her activities. In line with Harcourt and Donovan's (2005) findings, women can also be forced to work extra shifts when they have not earned enough money. In this context, they often work below the normal price or procure unprotected sexual services in order to obtain the required earnings, which in turn affects business in the RLD generally…”
mentioning
confidence: 55%
“…It is principally the two most recent reviews that inform this section (29,32). They both draw very similar conclusions, although they approach the issue from slightly different perspectives.…”
Section: Commercial Sex Workmentioning
confidence: 69%
“…HIV risk associated with CSW is, thus, highly contextually dependent, and this is well illustrated by a recent Vietnamese study which sampled sex workers from four border provinces. The prevalence of HIV among the sex workers ranged from 0% in a sample of 216 sex workers in one province, to 24% in a sample of 400 sex workers in another province (30) Notwithstanding the importance of sex work in the development of the HIV epidemic, there have been surprisingly few reviews of the determinants of sex work; exceptions include (28,29,31,32).…”
Section: Commercial Sex Workmentioning
confidence: 99%
“…Poorer sex workers and ones who choose to or are forced to service high numbers of clients are at higher risk for disease. Brothelbased sex work can have fewer risks since they provide greater security than what is possible on the streets, and brothel settings are more accessible to health and education services.Positive associations between alcohol use and 'unprotected sex' causative factor for the sexually transmitted diseases [13].81% were suffering from gastrointestinal problem which might be due to alcohol and drug related problems. Studies by Morgan [19] and Hill [20] have demonstrated the vulnerability of women to physical illness.…”
Section: Discussionmentioning
confidence: 99%
“…Age ranges of female street-based sex workers in Western countries have generally been reported to be teenage16 years up to mid-50s, and the mean age is typically late 20s to early30s [12,13].The older age of street-based sex workers may indicate a progression through different modes of sex work (such as escort, brothel and private work), Research in the U.K. provides support for the progression from private to street-based work among female sex workers [14].…”
Section: Discussionmentioning
confidence: 99%